2022
DOI: 10.1021/acs.macromol.1c01842
|View full text |Cite
|
Sign up to set email alerts
|

Polar Side Chains Enhance Selection of Semiconducting Single-Walled Carbon Nanotubes by Polymer Wrapping

Abstract: This paper describes the effectiveness of donor− acceptor (D-A) conjugated polymers to disperse and select for semiconducting single-walled carbon nanotubes (s-SWCNTs) when enhanced by the inclusion of polar oligoethylene glycolbased side chains, without altering the D−A backbone. We designed and synthesized two sets of naphthalenediimide(NDI)alt-bithiophene(T2)-based conjugated polymers with one of two alkyl side chains (decyl and dodecyl chains) of different lengths and with or without polar triethylene glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The synthesis routes and chemical structures of the two new conjugated polymers that were used to study the dispersion and discrimination of semiconducting carbon nanotubes are shown in Figure . The synthesis of PNDITEG-AH was carried out according to literature procedures . The monomers were synthesized and purified according to published procedures with slight modifications (see the Supporting Information for details). Both polymers were synthesized by a typical palladium-catalyzed Stille polycondensation of symmetrical dibromo naphthalene diimide and distannyl thienylennevinylene monomers.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The synthesis routes and chemical structures of the two new conjugated polymers that were used to study the dispersion and discrimination of semiconducting carbon nanotubes are shown in Figure . The synthesis of PNDITEG-AH was carried out according to literature procedures . The monomers were synthesized and purified according to published procedures with slight modifications (see the Supporting Information for details). Both polymers were synthesized by a typical palladium-catalyzed Stille polycondensation of symmetrical dibromo naphthalene diimide and distannyl thienylennevinylene monomers.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of electrical characteristics for the polymer wrapped s-SWCNT inks. (a–c) FET output characteristics for the examined inks for (a) a device fabricated from HiPCO: PNDITEG-AH (Adapted from our previous work), (b) HiPCO: PNDITEG-TVT , and (c) HiPCO: PNDIC8TEG-TVT . The arrows represent an increase in gate bias from 0 to ±50 V in steps of 10 V. (d) FET transfer characteristics for HiPCO: PNDITEG-AH (black), HiPCO: PNDITEG-TVT (red), and HiPCO: PNDIC8TEG-TVT (turquoise).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations